Ergonomic design of an EEG headset using 3D anthropometry. (January 2017) - Lacko, Daniël; Vleugels, Jochen; Fransen, Erik; Huysmans, Toon; De Bruyne, Guido; Van Hulle, Marc M.; Sijbers, Jan; Verwulgen, Stijn
Abstract: Although EEG experiments over the past decades have shown numerous applications for brain-computer interfacing (BCI), there is a need for user-friendly BCI devices that can be used in real-world situations. 3D anthropometry and statistical shape modeling have been shown to improve the fit of devices such as helmets and respirators, and thus they might also be suitable to design BCI headgear that better fits the size and shape variation of the human head. In this paper, a new design method for BCI devices is proposed and evaluated. A one-size-fits-all BCI headset frame is designed on the basis of three digital mannequins derived from a shape model of the human head. To verify the design, the geometric fit, stability and repeatability of the prototype were compared to an EEG cap and a commercial BCI headset in a preliminary experiment. Most design specifications were met, and all the results were found to be similar to those of the commercial headset. Therefore, the suggested design method is a feasible alternative to traditional anthropometric design for BCI headsets and similar headgear. Highlights: A one-size-fits-all BCI headset prototype was created using 3D anthropometric data. Most specifications for electrode fit, headset stability and repeatability were met. Electrode positioning deviated from ideal positions by 21.97 ± 10.44 on average. All results are within EEG general practice and similar to a commercial BCI headset. 3D anthropometry is a feasible design method for BCI headgear and near-body products.